?-Arrestin Promotes Wnt-induced Low Density Lipoprotein Receptor-related Protein 6 (Lrp6) Phosphorylation via Increased Membrane Recruitment of Amer1 Protein - Kriz, Vitezslav; Pospichalova, Vendula; Masek, Jan; Kilander, Michaela Brita Christina; Slavik, Josef; Tanneberger, Kristina; Schulte, Gunnar; Machala, Miroslav; Kozubik, Alois; Behrens, Jürgen; Bryja, Vitezslav (Journal of Biological Chemistry, 2014)
?-Arrestin is a scaffold protein that regulates signal transduction by seven transmembrane-spanning receptors. Among other functions it is also critically required for Wnt/?-catenin signal transduction. In the present study we provide for the first time a mechanistic basis for the ?-arrestin function in Wnt/?-catenin signaling. We demonstrate that ?-arrestin is required for efficient Wnt3a-induced Lrp6 phosphorylation, a key event in downstream signaling. ?-Arrestin regulates Lrp6 phosphorylation via a novel interaction with phosphatidylinositol 4,5-bisphosphate (PtdIns(4,5)P2)-binding protein Amer1/WTX/Fam123b. Amer1 has been shown very recently to bridge Wnt-induced and Dishevelled-associated PtdIns(4,5)P2 production to the phosphorylation of Lrp6. Using fluorescence recovery after photobleaching we show here that ?-arrestin is required for the Wnt3a-induced Amer1 membrane dynamics and downstream signaling. Finally, we show that ?-arrestin interacts with PtdIns kinases PI4KII? and PIP5KI?. Importantly, cells lacking ?-arrestin showed higher steady-state levels of the relevant PtdInsP and were unable to increase levels of these PtdInsP in response to Wnt3a. In summary, our data show that ?-arrestins regulate Wnt3a-induced Lrp6 phosphorylation by the regulation of the membrane dynamics of Amer1. We propose that ?-arrestins via their scaffolding function facilitate Amer1 interaction with PtdIns(4,5)P2, which is produced locally upon Wnt3a stimulation by ?-arrestin- and Dishevelled-associated kinases.
EVALuna2:10305